Решите пожалуйста (3m+4)(3m-4)-(3m+5)^2=-11 (6x+1)^2-(6x-1)^2=0 (4-5p)^2=(3-5p)^2-3

Решите пожалуйста (3m+4)(3m-4)-(3m+5)^2=-11 (6x+1)^2-(6x-1)^2=0 (4-5p)^2=(3-5p)^2-3
Гость
Ответ(ы) на вопрос:
Гость
(3m+4)(3m-4)-(3m+5)^2=-11 (3m)^2-4^2-(3m+5)^2=-11 9m^2-16-(9m^2+30m+25)=-11 9m^2-16-9m^2-30m-25=-11 -30m-41=-11 -30m=-11+41 -30m=30 m=30/(-30) m=-1. (6x+1)^2-(6x-1)^2=0 ((6x+1)-(6x-1))*((6x+1)+(6x-1))=0 (6x+1-6x+1)*(6x+1+6x-1)=0 2*12x=0 24x=0 x=0/ (4-5p)^2=(3-5p)^2-3 (4-5p)^2-(3-5p)^2=-3 ((4-5p)-(3-5p))*((4-5p)+(3-5p))=-3 (4-5p-3+5p)*(4-5p+3-5p)=-3 1*(7-10p)=-3 7-10p=-3 -10p=-3-7 -10p=-10 p=-10/(-10) p=1.
Не нашли ответ?
Ответить на вопрос
Похожие вопросы